Outcomes of Programmed Cell Death Protein 1 (PD-1) and Programmed Death-Ligand 1(PD-L1) Inhibitor Therapy in HIV Patients with Advanced Cancer. (1st January 2019) - Bari, Shahla; Muzaffar, Jameel; Chan, Austin; Jain, Sanjay R.; Haider, Ahmad M.; Adams Curry, Marjorie; Hostler, Christopher J.
Abstract : Due to HAART and consequent decline in mortality from infectious complications, HIV patients have an increasing burden of non-AIDS defining cancers. Data on their safety and efficacy is unknown as these patients were excluded from clinical trials due to concern of unforeseen side effects. Objectives . The main objective of our study was to evaluate the efficacy and safety profile of PD-1 and PD-L1 inhibitors in HIV patients being treated for advanced cancers and to assess the impact of these drugs on HIV status of the patients specifically CD4 count and HIV viral load. Materials and Methods . This was a retrospective analysis of data of 17 patients HIV treated with one of the PD-1/PD-L1 inhibitors (Nivolumab, Pembrolizumab, Atezolizumab, Durvalumab, or Avelumab) for advanced cancer. Results . 10 out of 17 patients responded to therapy. 7 patients, all of whom had shown response to therapy, were alive and 4 were still on checkpoint inhibitor. 10 patients including all 7 nonresponders had died. Responders had minimum of 15 weeks of response while one had ongoing continued response at 34 weeks. Side effects were seen in 7 patients and only one patient needed cessation of therapy. CD4 counts were stable on treatment while HIV RNA remained undetectable. Conclusion . PD-1 and PD-L1 inhibitors appear to have comparable efficacy and tolerable side effect profile and have no effect on HIV markers when used in HIV patients with advanced cancers.